Thymosin β4: A Multi-Faceted Tissue Repair Stimulating Protein in Heart Injury - Bjørklund, Geir; Dadar, Maryam; Aaseth, Jan; Chirumbolo, Salvatore (Current Medicinal Chemistry, 2020)
Thymosin Beta-4 (Tβ4) is known as a major pleiotropic actin-sequestering protein that is involved in tumorigenesis. Tβ4 is a water-soluble protein that has different promising clinical applications in the remodeling and ulcerated tissues repair following myocardial infarction, stroke, plasticity and neurovascular remodeling of the Peripheral Nervous System (PNS) and the Central Nervous System (CNS). On the other hand, similar effects have been observed for Tβ4 in other kinds of tissues, including cardiac muscle tissue. In recent reports, as it activates resident epicardial progenitor cells and modulates inflammatory-caused injuries, Tβ4 has been suggested as a promoter of the survival of cardiomyocytes. Furthermore, Tβ4 may act in skeletal muscle and different organs in association/synergism with numerous other tissue repair stimulating factors, including melatonin and C-fiber-derived peptides. For these reasons, the present review highlights the promising role of Tβ4 in cardiac healing.
Keywords: Central Nervous System